Analisis Penggunaan Etos Pathos Logos dalam Pidato Dedi Mulyadi di Upacara Hari Kebangkitan Nasional “Bangkit Bersama Wujudkan Indonesia Kuat” - Ardila, Della; Febria, Rhani (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
This study aims to analyze the elements of Aristotelian rhetoric, namely ethos, pathos, and logos, in Dedi Mulyadi's speech entitled "Rise Together to Realize a Strong Indonesia" which was aired on the KOMPASTV YouTube channel. This study uses a qualitative approach with a content analysis method to identify rhetorical strategies used by speakers in building persuasive power. The results of the study show that Dedi Mulyadi effectively combines the three elements of rhetoric. Ethos appears in 3 data, demonstrating the credibility and integrity of the speaker. Pathos was found in 5 data, highlighting an emotional narrative that evoked audience empathy. Logos is also present in 5 data, showing logical and factual arguments. The combination of these three elements creates a speech that is not only rational, but also emotional and moral. This speech proves that rhetoric is a powerful communication strategy in shaping public opinion and conveying messages effectively. Keywords: ethos, pathos, logos, dedi mulyadi.